(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
Uzbek national wedding ceremonies have been forming for centuries, enriched and developed, supplemented with modern elements. Any ritual is a social reality that develops and improves. National wedding ceremonies of the Uzbek people are an aesthetic reality that has its own evolutionary development. The scope of the wedding ceremony makes the functions it performs dynamic, artistic, emotional and aesthetically pleasing. Aesthetic tools, techniques and colors are also factors that make family celebrations, shows and weddings memorable and enjoyable. Marriage ceremonies were formed expressively, thanks to their freedom and devotion to love. The actions of marriage ceremonies began to be adopted in folk art using them on holidays. It should be noted that modern wedding ceremonies, as a novelty, have acquired various flaws that cast a small shadow on national values. The article provides a philosophical analysis of the need for a clear regulation of the development of national values and the preservation of rituals with an understanding of their essence.